2022
DOI: 10.1038/s41467-022-28404-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying TARP modulation of the GluA1/2-γ8 AMPA receptor

Abstract: AMPA-type glutamate receptors (AMPARs) mediate rapid signal transmission at excitatory synapses in the brain. Glutamate binding to the receptor’s ligand-binding domains (LBDs) leads to ion channel activation and desensitization. Gating kinetics shape synaptic transmission and are strongly modulated by transmembrane AMPAR regulatory proteins (TARPs) through currently incompletely resolved mechanisms. Here, electron cryo-microscopy structures of the GluA1/2 TARP-γ8 complex, in both open and desensitized states (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 85 publications
4
27
0
Order By: Relevance
“…In our ion binding analysis, we found distinct binding profiles of larger alkali ions (K + , Rb + and Cs + ) in the TTV part of the SF, while the larger vestibule at the upper part of the SF in NaK-CDI plays a much weaker role in binding and selectivity of ions. In line with this finding, our previous simulations 6 and recent cryo-EM data 36 of AMPA receptors revealed that the QQ part constitutes the major binding sites for monovalent ions, while the CDI part is wide and less important for coordination of monovalent ions with scarcely any metastable sites where ions reside. The present patch-clamp electrophysiology data showed that mutation of the CDI sequence in GluA2 by the DGNF of NaK had no obvious influence on channel activity, demonstrating again that the QQ filter in GluA2 is the most essential part of the SF for selection of monovalent ions.…”
Section: Discussionsupporting
confidence: 78%
“…In our ion binding analysis, we found distinct binding profiles of larger alkali ions (K + , Rb + and Cs + ) in the TTV part of the SF, while the larger vestibule at the upper part of the SF in NaK-CDI plays a much weaker role in binding and selectivity of ions. In line with this finding, our previous simulations 6 and recent cryo-EM data 36 of AMPA receptors revealed that the QQ part constitutes the major binding sites for monovalent ions, while the CDI part is wide and less important for coordination of monovalent ions with scarcely any metastable sites where ions reside. The present patch-clamp electrophysiology data showed that mutation of the CDI sequence in GluA2 by the DGNF of NaK had no obvious influence on channel activity, demonstrating again that the QQ filter in GluA2 is the most essential part of the SF for selection of monovalent ions.…”
Section: Discussionsupporting
confidence: 78%
“…Positive modulation is facilitated by F527A and by mutants in the lower part of M1, including V534A, F537A, R541A and F542A. Interestingly, this pattern correlates with M1-TARP interaction strength – the upper part of M1 is loosely coupled to γ8, while the region below Phe527 is coupled more tightly 38 . Moreover, this enhanced TARP modulation is not immune to NAM action, as positions distal from the binding pocket are also robustly blunted by all three NAMs, as shown for R541A and F542A ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Resolutions of the ion channel/TARP sector at ∼ 3.0 Å, with the LY-481 structure reaching 2.6 Å, enabled an unprecedented view of the modulator binding site with associated lipids and putative water molecules (Fig. In addition, we subjected these structures to large scale MD simulations in an explicit lipid membrane together with water and ions, alongside previously reported apostate complexes (open and resting; PDB: 7QHB and 7OCD, respectively) 22,38 . Three sets of simulations for each receptor, totaling 1.25-1.5 μs of sampling for each system, offered additional insight into ligand behavior in their binding pocket, as well as enabling a comprehensive comparison of local and global receptor dynamics in response to NAM binding (Supplemental Movie 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations